KEMAMPUAN NABI MUHAMMAD SAW. DALAM MERUBAH LINGKUNGAN MASYARAKAT ARAB JAHILIYAH: TINJAUAN PSIKOLOGI PENDIDIKAN - Ahmad Riyadh Maulidi; Muhammad Syukri; Annisa Fadila Mardhatillah (Psyche: Jurnal Psikologi, 2022)
According to psychological theory, two forms of interaction between humans and the environment, namely humans can be affected by the environment can be found by humans. The campaign that a good environment will bring good changes for individuals is being carried out. Vice versa, if the environment is bad, then the individuals in that environment are also bad. It is interesting for researchers to see further how the ability of the Prophet Muhammad SAW. in changing the environment of the Arab society of ignorance. Living in the midst of moral decline does not make him affected by the environment. it is the environment that has changed because of his presence. The method used is the library method with a qualitative approach. Psychological theory related to environmental analysis with the ability of the Prophet Muhammad. in changing the Arab environment of ignorance. The results showed that there was a relationship between the psychological perspective on the environment and the ability of the Prophet Muhammad. in changing the Arab environment of ignorance. There are two reasons why the Prophet Muhammad SAW. able to change the Arab environment of ignorance and not be influenced by it, namely because of his status as an Apostle who carries Islamic teachings and noble character who can be an example. It should be in education. Good teaching materials and examples brought by our parents and teachers are a top priority in the educational process today.